Fatty Acid Composition, Phospholipid Molecules, and Bioactivities of Lipids of the Mud Crab Scylla paramamosain - Thi Phuong Lan Nguyen; Van Tuyen Anh Nguyen; Thi Thanh Trung Do; Trung Nguyen Quang; Quoc Long Pham; Tat Thanh Le (Journal of Chemistry)
The mud crab increases the yield of farming in Southeast Asian countries. Scylla paramamosain, one of four mud crab species belonging to the Scylla genus, is a rich nutrient source during its soft-shell moulting period. In this study, we analysed the total lipid content, fatty acid components, and phospholipid molecular species of the S. paramamosain mud crab. The total lipid content was 1.62 ± 0.08%, which is similar to that of S. serrata previously reported. Twenty-one fatty acids were identified in S. paramamosain. The composition and molecular forms of the phospholipids were identified using high-performance liquid chromatography-high-resolution mass spectrometry. Fifty-four different molecules belonging to six types of phospholipids were identified. Notably, phospholipids were made of fatty acids with C16 : 0; C18 : 0; C20 : 4; C20 : 5; and C22 : 6 main components. The anti-inflammatory and cytotoxic effects of crab lipids and phospholipids were investigated for the first time. The anti-inflammatory activity of the total and polar lipids had IC50 values of 71.5 and 68.6 μg/mL, respectively. The crab polar lipid fraction, which contained phospholipids, also presented high cytotoxic activity toward five cancer cell lines with IC50 values ranging from 85.4 to 95.8 μg/mL.